PENGARUH WORKPLACE LONELINESS TERHADAP KINERJA YANG DIMEDIASI OLEH WORK ALIENATION PADA PERAWAT RSUD CUT NYAK DHIEN MEULABOH - Saumi rahmawati; Amri Amri (Departemen Manajemen, 2021)
This study aims to measure the effect of Workplace Loneliness toward Employee Performance mediated by Work Alienation on nurses of RSUD Cut Nyak Dhien Meulaboh.. The sample used in this study were nurses of RSUD Cut Nyak Dhien Meulaboh amounted for 169 respondents. The data equipment used in this study was a questionnaire. The sampling technique used is Probability Sampling. Hierarchical Linear Modeling (HLM) is used as the method of analysis to examine the effect of all the variables involved.Based on the results of the HLM analysis, it indicates that Workplace Loneliness has a positive effect on Performance and Work Alienation. Work Alienation has a positive effect on Performance and mediated the relationship between Workplace Loneliness and Performance.